Novel betulin derivative is responsible for the anticancer folk use of Ziziphus spina-christi from the hot environmental habitat of UAE. (1st March 2019) - Soliman, Sameh; Hamoda, Alshaimaa M.; El-Shorbagi, Abdel-Nasser A.; El-Keblawy, Ali A.
Abstract: Ethnopharmacological relevance: Several natural products derived from plant sources are developed to remarkable medicines based on their traditional uses. Ziziphus, a worldwide known plant, is proven for potential cytotoxic activity. However, the plant growing at the unique hot environmental climate of UAE was never investigated. Different phytochemicals may be produced from the same plant genotype at different climates leading to variable pharmacological activities. Aim of the study: The study was conducted in order to investigate phytochemicals in the UAE native Z. spina-christi plant and its anticancer activity. Materials and methods: Z. spina-christi plant were collected, dried and dissected into leaves, stems and thorns. The plant organs were subjected to comparative fractionation-based anticancer assay followed by spectroscopic analysis of a uniquely isolated compound. Results: The results indicate that a novel betulin derivative (13-dehydrobetulin) isolated from plant stem exhibited substantial anticancer activity specifically against liver cancer and with wide therapeutic range. Conclusions: Growth of cytotoxic traditionally-known plant remedy at harsh environmental habitat advances its anticancer activity due to production of novel phytochemical with optimum activity and minimal toxicity. Furthermore, such approach may be a future to develop novel lead compounds with optimum activity. Graphical abstract: